In Search of a Solution:: An Independent Human Rights Team and Its Legitimacy in (West) Papua, Indonesia - Latuputty, Milena (Journal of Human Rights and Peace Studies, 2020)
This article discusses findings the of thesis research into potential challenges to the legitimacy of an independent human rights team among Papuan civil society in Indonesia. It aims to provide an answer to the question whether it is conceivable that a team of local civil society actors, appointed by the State to work independently on human rights cases, gains legitimacy among Papuan civil society. In the past, justice mechanisms to address human rights abuses in Papua have been without effect, and the current relationship between Indonesia and its Papuan community has been shaped by a history of political debate and continuous outbreaks of violence. This status quo could threaten the legitimacy of a State-appointed human rights team and compromise its stable existence. The research was based on a grounded theory approach, and identified and analysed the key indicators of legitimacy among a sample group of informed Papuan indigenous civilians. Qualitative field research was performed in May-June 2017, by conducting interviews among indigenous Papuan people and local civil society experts, substantiated with extensive documentary research.